Pengaruh Perilaku Berfoto di Obyek Wisata terhadap Kebahagiaan Wisatawan - Saptin Dwi Setyo Hastuti (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2017)
In these recent years, the prospect of photography is increasing. It also influences the tourism industry. Photography also has an important role in the development of the tourism industry. This research aims to investigate (1) the factors influencing tourist’s behaviour in taking a photo, (2) the activities after taking a photo, (3) and the influence of tourist’s behaviour in taking a photo on their happiness. This research was survey research. The locations of this research were in Malioboro, Hutan Pinus, Tebing Breksi, Kalibiru, and Gunung Api Purba Nglanggeran. The population comprised the visitors of those places. The sample was taken by applying the sample non-probability technique due to the unavailable visit data. The sample for each place was 80. Thus, the whole sample was 400. The survey was conducted from April – May 2017. The data were collected through a questionnaire. The data were analysed by applying descriptive statistics and crosstab in the SPSS 16. The result of the research shows that the factors influencing the tourists’ photo behaviour are the scenery or background of the place, the condition and completeness of facilities, the provided photo spot, the photoactivity, and the access post photo. Furthermore, the result also shows that the activities after taking the photo were the speed of publishing the photo, the editing, dan publishing photo in Instagram. Last, the tourist’s taking photo behaviour influencing the happiness were because of the reason of taking a photo, taking a photo at a different spot, taking many photos, and the quality of the photo